A descriptive analysis of the Pangasinan prefixes - Abayari, Aurora Z. 1924- (1969)
This paper described the prefixes with the hope of contributing to the other existing descriptions and of helping the Pangasinan teachers of English construct effective instructional materials. Data were gathered from informants who are native speakers of Pangasinan. The prefixes in Pangasinan are rather extensive in use and scope and complex in form and meaning. They are bound forms and are either derivational or inflectional in nature. The prefixes in Pangasinan perform varied functions: they change one class of root words or stems to different classes of words; and they classify root words and stems or modify their meanings. Some prefixes give some verbs a past or a future meaning.
"June, 1969."
Vita.
Thesis (M.A.T. English as a Second Language)--University of the Philippines, Diliman.
Keywords: Kapampangan language -- Suffixes and prefixes